THE FACTORS INFLUENCING THE INTOXICATED: A STUDY OF SMALL SCALE FISHERMEN IN MANNAR DISTRICT - Pushpanathan, A. (University of Kelaniya, 2012)
Alcoholism is dangerous among young people and the elderly, because the symptoms are not easily recognized until the affected person becomes truly alcohol dependent.A man takes alcohol or drugs for recovering from some problems temporarily, and to forget worries, frustration, and losses employment, family members and assets in his life. Chronic diseases, poverty, lose of property, separation from family are main effect of taking intoxicates. The fishermen believe thatalcohol helps to do hard work in the sea. The main objective of this study is to analyze the factors influencing the intoxicated. Four factorswere identified in this study, such as wrong perception, family influence, wrong peer pressure, social issues. The present study especially analysis the small scale fishermen in Mannar District. The data were collected from small scale fishermen those who recovered from the treatment atthe Centre for Rehabilitation of Alcoholics and Drug Addicts in Mannar District. The data were analyzed using the Principle Component factors with VarimaxRorated Method. KMO and Bartlett’s test were adopted for adequacy of data. Findings of this study indicated that the being tired out of hard work, recovering from diseases, and gaining more income in wrong perception, negligence by children, separation from family, and negligence by wife in family,Learn from friend, and No avoiding pressure from friendshipin wrong peer pressure, and child abuse, and poverty in social issues are more influencing factors on intoxicated.
Keywords: Family; Intoxicated; Social issues; Wrong perception; Wrong peer pressure